COMPETENŢELE INTERCULTURALE: DEFINIRE ŞI PARTICULARITĂŢI - USM ADMIN (Moldova State University, 2008)
The concept of "competence" can be deduced from the phenomenon of competence, in general, a process that is initiated, produced among cultures, needs understanding, appreciation, capitalization of culture, respect based on infor- mation, curiosity for ethnical culture, interpersonal relation, where every person has it's own individual identity.